Seseli foliosum (Somm. et Levier) Manden.—A Comprehensive Phytochemical and Biological Evaluation - Mariam Nersezashvili; Dali Berashvili; Malkhaz Jokhadze; Mariam Metreveli; Łukasz Świątek; Kinga Salwa; Łukasz Pecio; Krzysztof Kamil Wojtanowski; Adrianna Skiba; Izabela Korona-Głowniak; Gökhan Zengin; Krystyna Skalicka-Woźniak (Molecules)
The genus Seseli L. (Apiaceae family) is widespread across Europe and Asia, with ten species identified in Georgia. Among these, Seseli foliosum (Somm. et Levier) Manden., is notable for its unique pharmacological properties. To our knowledge, comprehensive phytochemical and biological investigations have not yet been conducted. The primary aim of this research is to explore the chemical and biological properties of S. foliosum, thereby enhancing its potential applications in medicine and related fields. Different chromatographic techniques were utilized to isolate individual compounds and to identify the chemical composition of S. foliosum MeOH and Et2O extracts from seeds and roots. A battery of biological assays (antimicrobial, antioxidant, enzymatic, anxiolytic, and cytotoxic) were employed to assess the pharmacological properties of the extracts. The results from gas chromatography with mass spectrometry (GC/MS) revealed that both MeOH and Et2O extracts contain a diverse array of compounds, including monoterpenoids, sesquiterpenoids, and phenolic compounds. Furanocoumarin edultin was isolated from the MeOH extract by liquid–liquid separation (LLS). The MeOH extracts exhibited important antioxidant, enzyme inhibitory, and antimicrobial activities with notable efficacy against Staphylococcus aureus (MIC 125 µg/mL) and Candida glabrata (MIC 62.5 µg/mL). Underground Et2O extracts showed advanced cytotoxic activity, particularly against hypopharyngeal carcinoma cells (CC50 22.33 µg/mL and 27.16 µg/mL, respectively). The study provides a wide-range analysis of the phytochemical composition and biological activities of S. foliosum, highlighting its potential as a source of bioactive compounds. These findings contribute to the understanding of the therapeutic potential of S. foliosum and lay the groundwork for further pharmacological and clinical research.